Studi Literatur: Literasi Keuangan pada Penggunaan Pinjaman Online - Hamidah, Nur; Pahala, Indra; Gurendrawati, Etty (Neolectura, 2023)
The purpose of this study is to find out how financial literacy impacts online loan financial technology. This research uses the systematic literature review (SLR) methodology which is a research design to identify, assess and interpret the search results of research reviews systematically. This research originates from six studies spanning several years. The results of the literature study show that consumers still need to understand financial literacy because it will have an impact on how to manage and use financial technology.